Introducing usability requirements in a test/model-driven web engineering method - Robles Luna, Esteban
The success of web applications is constrained by two key features: usability and fast evolution. Current web engineering approaches follow a unified development style which tends to be unsuitable for applications that needs to evolve fast. In this paper, we show how to address usability requirements in an agile test/model driven web engineering method. Usability requirements are contemplated from the very beginning of each cycle by creating a set of meaningful tests that drive the development of the application and ensure that no functionality is altered unintentionally through development cycles. The approach is illustrated with an example in the context of the WebML / WebRatio suite.